THE EFFECT OF PROBLEM SOLVING MODEL AND SCORING TYPE OF MULTIPLE-CHOICE FORMATIVE TESTS ON STUDENT HIGH ORDER THINKING SKILLS (HOTS) ABILITY - andi taufiq umar (LPPM Universitas Negeri Jakarta, 2018)
Abstract : This research is a type 2x2 factorial design that aims to see the correlation between problem solving model and scoring type of multiple choice formative test in improving students' HOTS capability in Chemistry lesson. Type of scoring test is divided into two sub-variables that scoring by scores and scores are appropriate while the learning model consists of problem solving model and direct learning model. The student's HOTS capability consists of three stages of cognitive namely analysis, evaluation, and synthesis by using choice of choice test with several HOTS answer choices that have been validated by experts and panelists. The population in this study is all students of SMA Negeri in East Luwu regency. Sampling was done by cluster random sampling with total sample of 80 students who were integrated into empathy groups consisting of 20 samples per group. The result of analysis shows that FO value in main effect test and interaction effect is bigger than Ftable value is 3,968 which show the influence of interacation between problem solving model and scoring type to students’s HOTS ability.